Microencapsulation of orange-fleshed sweet potato (Ipomoea batatas) carotenoid extract by spray-drying with maltodextrin and whey protein concentrates - Saefullah Thaher; Sri Anggrahini; Chusnul Hidayat; Hari Hariadi (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
Orange-fleshed sweet potato (Ipomoea batatas) carotenoids were encapsulated in maltodextrin and whey protein concentrates by spray-drying to promote dispersibility in water and looked for the best encapsulant concentration in both encapsulants. The moisture content, wettability, hygroscopicity, color characterization, cold water solubility, and encapsulation efficiency were analyzed for encapsulant concentration of 10%, 20%, and 30% (w/v). The encapsulant concentration of 20% showed the best result with 6.09% moisture content, 11.07 hygroscopicity, 51 s wetting time, 94.50% cold water solubility, and 81.52% encapsulation efficiency for maltodextrin encapsulant. While whey protein concentrates encapsulant gave the result of 6.35% moisture content, 12.44% hygroscopicity, 148.8 s wetting time, 93.13% cold water solubility, and 82.02% encapsulation efficiency. The diffractogram from XRD showed that microcapsule had the amorphous phase dominant and indicated high solubility in water matrix. The microcapsule using maltodextrin encapsulant has smoother and more spherical morphology than microcapsule using whey protein concentrate encapsulant. The color characterization of 30% was lighter, less red, and less yellow than the others based on L*, a*, and b* value respectively. The carotenoid with 20% encapsulant concentration was well encapsulated enough and the addition of more than that did not produce significantly better results.